Transarterial chemoembolisation and radioembolisation for the treatment of primary liver cancer and secondary liver cancer: A review of the literature. Issue 3 (3rd March 2014) - Bester, Lourens; Meteling, Baerbel; Boshell, David; Chua, Terence C.; Morris, David L.
Summary Liver‐directed therapies are continuing to evolve in the field of interventional oncology and are gaining increasing use in the treatment of unresectable primary and secondary liver cancers. In this article, we review two liver‐directed therapies that are currently used for the palliative treatment of primary and secondary hepatic tumours: transcatheter arterial chemoembolisation (TACE), including a new type of TACE with drug‐eluting beads (DEB‐TACE), and radioembolisation. The concept of these transcatheter intraarterial therapies is to selectively deliver high doses of anticancer treatment to the tumour. While TACE delivers one or more chemotherapeutic drugs into the hepatic arteries supplying the tumour, radioembolisation uses non‐embolic microspheres incorporating the radioactive isotope 90Y. In this article, we discuss some technical aspects, patient selection, current clinical evidence, and future directions of TACE, TACE with drug‐eluting beads (DEB‐TACE) and radioembolisation for primary and secondary liver cancer.